Avenging child sex abuse: vigilante violence in prisons and the community - Long, Joshua Shane (Routledge, 2024)
This book explores the subjects of child sex abuse, flaws in the justice system, cultural support for vigilantism, prison violence, and the socio-legal philosophy of punishment